97. Towards a dose-response correlation in radioiodine therapy of hyperthyroidism from nodular thyroid disease. (December 2018) - Pacilio, M.; Ventroni, G.; Frantellizzi, V.; Cassano, B.; Montesano, T.; Borrazzo, C.; Basile, C.; Mango, L.; De Vincentis, G.
Abstract : Purpose: Dosimetric treatment optimization is recommended for radioiodine therapy of hyperthyroidism. However, many clinicians still claim that fixed activity administrations yield analogous effectiveness, sparing time-consuming pretherapeutic studies. The possibility to establish a dose-response correlation was here investigated, highlighting the added value of patient-specific dosimetry. Methods: 374 patients affected by autonomous thyroid nodule, or multinodular goitre – presenting abnormal blood tests (TSH, and/or FT3, FT4) – were treated. Post-therapy follow-up lasted for at least 1 year. 187 patients were treated with an empiric methodology (not basing on a pre-treatment dosimetric study). 187 patients underwent dosimetry-based treatments (collecting just three biokinetics points), including also 67 treatments based on a biologically effective dose (BED) prescription. The normality of blood tests at 1 year from the therapy, after the first treatment, was evaluated. The BED was also used in the result analysis for all dosimetry-based treatments. Statistical analysis was performed by Mann-Withney and Chi-squared test, univariate receiver operating characteristics (ROC) analysis, and interpolation of dose–response data by a logistic model. Results: Dosimetric differences between the unhealed and the healed group (p = 0.0067) resulted from the 120 treatments based on absorbed dose prescriptions, also after conversion of the absorbed dose values in BED (p = 0.0049): the Area-under-curve (AUC) was 0.758 and 0.770, respectively. No significant differences were observed for the healing probability between the BED- or absorbed dose-based treatments (p = 0.423). Considering the total 187 dosimetry-based treatments, the absorbed dose/BED-response curves showed regular trends with r-value of 0.979 and 0.977, respectively. The absorbed dose associated to a healing probability of 50% and 95%, was 42.6 Gy and 242.3 Gy, respectively. The probability of recurrence was 9.6%, exactly half of that associated to the empiric treatment group (19.3%, p = 0.0081). Conclusions: Patient-specific dosimetry has proven to increase therapeutic effectiveness, reducing the recurrence frequency and the need of repeated treatments.